The Katyń Massacres before the European Court of Human Rights: From Justice Delayed to Justice Permanently Denied. (November 2015) - Kamiński, Ireneusz C.
The Polish case of Janowiec and Others v. Russia was initiated by a group of close relatives of victims of the 1940 Katyń Massacres. Only in 1990 did the Soviet Union recognize that it had perpetrated the massacres. The applicants in the Janowiec case alleged that the Russian investigation into the massacres, which commenced in 1990 as transparent proceedings but was terminated in 2004 in secrecy, cannot be considered effective under the Convention. Furthermore, inasmuch as the Russian military prosecutors and courts held that the Polish prisoners-of-war "had disappeared" in the spring of 1940 or—if "hypothetically" killed—there might have existed just cause for such an execution, the applicants complained that such statements denied established historical facts and were tantamount to the denigrating and inhuman treatment prohibited by the Convention. The Grand Chamber judgment was not in the applicants' favor. By a majority, the judges either declined to hear the case on its merits or held that there had been no violation of the Convention, turning—as the four minority judges wrote in their dissent—"the applicants' long history of justice delayed into a permanent case of justice denied." This article is a personal account of the principal lawyer acting on behalf of the applicants in the Janowiec case.